Profile of Mild Acne Vulgaris Patients at Tertiary Hospital at Surabaya, Indonesia - Arifin Saiboo, Alvian; Muhammad Yulianto Listiawan; Sari, Maylita; Indramaya, Diah Mira; Murtiastutik, Dwi; Damayanti; Anggaraeni, Sylvia (Faculty of Medicine, Universitas Airlangga, 2024)
Background: One of the most prevalent skin conditions worldwide is acne vulgaris (AV). Even mild forms of AV could have an adverse impact on psychological wellbeing. Purpose: To explore the profile of mild AV patients in a tertiary care facility in Surabaya, Indonesia. Method: This was a descriptive study conducted for eight weeks. Data regarding the patient's identity, history, skin type, and complaints related to AV or other complaints that arose were noted on the sample's medical record and collected for analysis. The Lehmann classification was used to assess the AV degree. Result: A total of 34 patients were included. Gender equality was similar in our study, and late adolescence (17-25 years) is the most dominant age group (73.5%). Genetics plays the biggest precipitating factor (73.5%), followed by stress (70.6%). Most patients had an oily skin type (91.2%) with Fitzpatrick's phototype 4 (85.3%). Comedone is the most prevalent lesion in our study (median = 10, range = 4-20). Conclusion: Most patients with mild AV had an oily skin type, and late adolescent is most dominant age group.